Instilling A Culture Of Modesty And Respect For The Opposite Sex Through Gender-Based Classroom Segregation Policies In Elementary Schools - Astiti Yugianti; Bambang Budi Wiyono; Ahmad Yusuf Sobri (At Turots: Jurnal Pendidikan Islam, 2026)
Character education is a fundamental aspect in the formation of students' personalities in primary schools, especially in the midst of increasing social challenges such as sexual harassment and lack of respect between genders. Data from reports from the Ministry of Women's Empowerment and Child Protection (KPPPA) and the Federation of Indonesian Teachers' Unions (FSGI) show an increase in cases of harassment and bullying among elementary school-age students, so preventive measures through appropriate educational policies are needed. This study aims to explore the effectiveness of gender-based classroom segregation policies in strengthening cultural values of shame and respect for the opposite sex as part of character education. A descriptive qualitative research approach was used with data collection through observation, in-depth interviews and documentation in elementary schools that have implemented this policy. The results show that gender-based classroom segregation contributes significantly in shaping students' character, particularly in internalizing shame and mutual respect between genders. In addition, this policy also has the potential to reduce the risk of sexual harassment behavior in the school environment. The implication of this research confirms the importance of a gender-based policy approach in supporting more effective character education in primary schools, as well as providing practical recommendations for the development of educational policies oriented towards strengthening social and moral values in educational institutions.